Analysis of Determinants of Development Imports in Indonesia - Malem Ateta Br. Purba; Muhammad Fitri Rahmadana; Fitrawaty Fitrawaty (Budapest International Research and Critics University, 2021)
Indonesia is known as a developing country which industrial production has not been sustainable to the local demand. This is reflected in Indonesia's dependence on other countries in terms of consumer goods, raw and auxiliary materials as well as capital goods. Indonesia carries out import activities because most domestic products have not been able to compete with foreign products, and there is a sense of grandeur for the people when they are able to buy goods from abroad. The purpose of this study is to analyze the effect of gross domestic product (GDP), foreign exchange reserves, exchange rates and inflation on imports in Indonesia in 2000 - 2019. The method of analysis in this study uses the Error Correction Model (ECM). The estimation results show that in the short term, the variable gross domestic product (GDP), foreign exchange reserves and inflation have a positive and significant effect on imports in Indonesia, while in the long run, all variables have a significant and significant effect on imports in Indonesia. In this case, the support of the government and producers by providing good quality production will greatly assist in the development of the domestic industry, so that the Indonesian people turn to domestic products again.